Volume 7A: Structures and Dynamics 2017
DOI: 10.1115/gt2017-63444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vortex Shedding on the Performance of Scoop Based Lubrication Devices

Abstract: In civil aircraft aeroengine bearing chambers it is sometimes difficult to feed oil to bearings using the traditional under-race or targeted jet approaches. In such situations one proposed solution is that of a scoop delivery system. Published experimental investigations into scoop performance show that scoop collection efficiency (the percentage of oil delivered by the scoop system to its destination compared to that supplied by the feed jet) is a function of many operational and geometric parameters. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Korsukova and Morvan have compared semi-3D and two-dimensional numerical simulations, and their results show that both models can reflect typical two-phase flow characteristics inside an under-race lubrication system [13]. In addition, some studies have also proved that two-dimensional numerical simulations can reasonably predict the internal flow and oil collection performance of an under-race lubrication system [6][7][8][9]11]. To improve the calculation efficiency while ensuring prediction accuracy, a two-dimensional numerical calculation model was established for the middle section containing the main structural features of the oil jet nozzle and the radial oil scoop, as is shown in Figure 2.…”
Section: Computational Domain and Meshmentioning
confidence: 99%
See 1 more Smart Citation
“…Korsukova and Morvan have compared semi-3D and two-dimensional numerical simulations, and their results show that both models can reflect typical two-phase flow characteristics inside an under-race lubrication system [13]. In addition, some studies have also proved that two-dimensional numerical simulations can reasonably predict the internal flow and oil collection performance of an under-race lubrication system [6][7][8][9]11]. To improve the calculation efficiency while ensuring prediction accuracy, a two-dimensional numerical calculation model was established for the middle section containing the main structural features of the oil jet nozzle and the radial oil scoop, as is shown in Figure 2.…”
Section: Computational Domain and Meshmentioning
confidence: 99%
“…Prabhakar [11] found that the flow capacity of the oil capture passage increases as the outlet pressure decreases. When the pressure difference is 0.18 bar, the oil capture efficiency increases by 7%.…”
Section: Introductionmentioning
confidence: 99%
“…Prabhakar et al [19] evaluated the capture efficiency using conventional CFD. Two parameters were investigated in an attempt to reduce the plume formation and to improve the capture efficiency.…”
Section: Research On Scoopsmentioning
confidence: 99%
“…Paloma [6] researched on the capability of a scoop system to capture and retain delivered oil. Prabhakar and Abakr [7] demonstrated that oil loss due to the centrifugal effect is influenced by the location of the oil jet impacting the inner surface of the blade. Korsukova and Morvan [8] studied the radial under-race lubrication structure and found that oil collection efficiency decreases significantly when the oil impinges on the outer surface profile near the blade tip but improves when it impacts the outer surface contour near the blade root.…”
Section: Introductionmentioning
confidence: 99%